Implementación parcial del Sistema de gestión de inocuidad alimentaria ISO 22000 en Productos Alimenticios DIMAR Ltda (2009)
Productos Alimenticios DIMAR Ltda. identified its customers’ needs for safe products. That´s the reason why they decided to implement the Harmlessness Management System under the ISO 22000 Standard. The system structure starts with the good manufacturing practices implementation, then the risks and critical control points analysis and, finally, management requirements, documents and improvement. This research shows the developed process until the good manufacturing practices application; they are the set of requirements needed to start the risks and critical control points analysis. Other stages will be developed according to the work plan established by the company. The project results are presented in three levels: 1) Adressing, 2) Prerequisite programs that allow the company to control de production process and 3) Investment budget. The research shows that the commitment with the Harmlessness Food System demands organizational guidelines and institucional goals which support it